Investigating sustainable approaches to late maturity and fungal infection of organic ‘Medjool’ date palm (Phoenix dactylifera L.) fruit in the Western Cape, South Africa - Peddie, Rude Jo-Anne (Stellenbosch : Stellenbosch University, 2023)
Thesis (MScAgric)--Stellenbosch University, 2023.